1998
DOI: 10.1021/ac980014b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lithium Sulfate as an Unsymmetrical-Valence Salt Bridge for the Minimization of Liquid Junction Potentials in Aqueous−Organic Solvent Mixtures

Abstract: The transference numbers t of lithium sulfate in acetonitrile/water and methanol/water solvent mixtures have been studied by measuring the emfs of such transference cells as Pb(Hg)|PbSO(4)|Li(2)SO(4) (m(2))||Li(2)SO(4) (m(1))|PbSO(4)| Pb(Hg), Hg|Hg(2)SO(4)|Li(2)SO(4) (m(2))||Li(2)SO(4) (m(1))|Hg(2)SO(4)|Hg, and Li(x)Hg(1-)(x)|Li(2)SO(4) (m(1))||Li(2)SO(4) (m(2))|Li(x)Hg(1-)(x), in view of characterizing Li(2)SO(4) as an unsymmetrical salt bridge for the minimization of liquid junction potentials in potentiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…[36] Over the past decade, DFT and ab initio calculations on [Li(CH 3 CN) n ] + and related clusters were also performed by different groups. [30,[37][38][39][40] There has been a special interest in the properties of Li salts, such as conductivity, [41][42][43][44] transport abililty, [45][46][47] viscosity, [48] and osmotic behaviour [49] , in solvents and solvent mixtures because of the use of Li + ions in batteries of high energy density. [50] Such studies are not restricted to liquid systems.…”
Section: Introductionmentioning
confidence: 99%
“…[36] Over the past decade, DFT and ab initio calculations on [Li(CH 3 CN) n ] + and related clusters were also performed by different groups. [30,[37][38][39][40] There has been a special interest in the properties of Li salts, such as conductivity, [41][42][43][44] transport abililty, [45][46][47] viscosity, [48] and osmotic behaviour [49] , in solvents and solvent mixtures because of the use of Li + ions in batteries of high energy density. [50] Such studies are not restricted to liquid systems.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, a prerequisite is the availability of appropriate SO 4 2--based salt bridges. This unsymmetrical salt bridge does exist: it is a concentrated Li 2 SO 4 solution, as it has been recently proven by Faverio and Mussini [5]. As it was pointed out earlier by Mussini [6], any binary (z + : z − )−valent salt used for minimizing liquid junction potentials must be "equitransferent".…”
Section: Thermodynamic and Electroanalytical Characterization Of The mentioning
confidence: 72%
“…None of the other alkali metal sulfates satisfies the above condition. Using a Li 2 SO 4 salt bridge of m = 2 mol·kg -1 (whose ionic strength is 6 mol·kg -1 , i.e., higher than that of the saturated KCl), Faverio, Mussini, and Mussini [5] found that the working potential of the mercury|mercurous-sulfate reference electrode is 0.6327 V at 25 °C, and that of the lead-amalgam|lead-sulfate treated here is −0.3327 V.…”
Section: Thermodynamic and Electroanalytical Characterization Of The mentioning
confidence: 83%
See 2 more Smart Citations